Responses of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) to host plant cues and sex pheromones in Africa - Weldon, Christopher W. (University of Pretoria, 2023)
Thesis (PhD (Entomology))--University of Pretoria, 2023.